Perlindungan Hukum dalam Perjanjian Franchise: Legal Protection in Franchise Agreements - Estu Nur Ikhsan; Rafli Febriansyah; Rafiq Maulana; Fatur Ilham Hariyanto (Jurnal Hukum Bisnis, 2026)
Franchise contracts in Indonesia are rapidly developing as a growth instrument for micro, small, and medium enterprises. However, their practice often places franchisees in a weaker position than franchisors, exposing them to the risk of default, unilateral termination, and unclear intellectual property rights, resulting in minimal legal protection and contractual certainty. This study aims to examine legal protections in franchise agreements, assess the balance of rights and obligations, evaluate the effectiveness of dispute resolution mechanisms, and assess the contract's compliance with applicable legal regulations in Indonesia. The study employs a normative juridical approach, using a literature review and legal document analysis, including local and international franchise contracts and related regulations, as well as scientific literature and research from the past five years. Content analysis was conducted to assess legal certainty, contractual fairness, and legal protection for franchisors and franchisees. The results indicate that franchise contracts remain formal, emphasize franchisee obligations, and lack preventive protection; some clauses are unclear regarding intellectual property rights and dispute resolution procedures. Franchisors have dominant control, while franchisees face limited rights and the risk of legal disputes. Contract reformulation is needed, including granting franchisees limited control rights, detailed mediation and arbitration procedures, strengthening intellectual property rights, and harmonizing contracts with legal regulations. This study confirms that legal protection in franchise agreements in Indonesia is suboptimal and that more balanced, procedural, and transparent contracts are urgently needed to increase legal certainty, fairness, and a more balanced relationship between franchisors and franchisees, while minimizing legal and operational risks.